The Effect of Discipline and Training on Employee Performance at PT. BCA Finance in Jakarta - Yayuk Karliena; Suharno Suharno; Eka Febrianata; Cecep Warman; Desty Endrawati Subroto (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of discipline and training on employee performance at PT. BCA Finance in Jakarta. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. This study's results find that the discipline and training on employee performance at PT. BCA significantly affects employee performance by 47.3%; hypothesis testing is obtained t count> t table or (8.683> 1.989). Training has a significant effect on employee performance by 43.6%; hypothesis testing is obtained t count> t table or (8,054> 1,989). Discipline and training simultaneously have a significant effect on employee performance with the regression equation Y = 8.758 + 0.404X1 + 0.373X2, and the contribution of the effect is 56.1%, hypothesis testing obtained F count> F table or (52.947> 2.710).